Enhancement of photo-thermal conversion using gold nanofluids with different particle sizes. (15th March 2016) - Chen, Meijie; He, Yurong; Zhu, Jiaqi; Kim, Dong Rip
Highlights: Au NPs with different sizes were synthesized by a seed mediated method. Au NPs were added to improve the photo-thermal conversion efficiency. Properties of two collector models were discussed and compared. The size effects of Au NPs on photo-thermal conversion were discussed. Abstract: This work describes an experimental study of the particle size dependence of gold nanofluids during photo-thermal conversion in a direct absorption solar collector (DASC). Au nanoparticles (NPs) with different sizes were synthesized using a seed mediated method. Au NPs play a significant role in enhancing the solar light absorption with respect to a pure base fluid at a very low concentration due to the localized surface plasmon resonance effect. Experimental results of the photo-thermal conversion showed that the photo-thermal conversion efficiency of Au nanofluids obtained an average enhancement of 19.9% and 21.3% for a cube shaped DASC and a flat shaped DASC, respectively, compared with H2 O at a relatively low mass fraction (∼0.000008% weight). Reducing the Au NP size led to the enhancement of the photo-thermal conversion efficiency under the present experimental conditions, which could be an effective way for the modification of optical properties and thermodynamic characteristics. However, the size of Au NPs did not significantly influence the efficiency for the cube shaped DASC. The cube shaped DASC model usually had the higher efficiency than the flat DASC model using the same working fluids since the heat loss percentage of the cube shaped DASC was lower.